2013
DOI: 10.1111/1467-954x.12016
|View full text |Cite
|
Sign up to set email alerts
|

Political Parties' Perceptions and Uses of Anti-Semitic Conspiracy Theories in Turkey

Abstract: Despite its ever‐present and at times escalating significance, conspiracy theory is an under‐researched topic in the social sciences. This paper analyses the political influence of conspiracy theories by drawing on semi‐structured interviews with the representatives of four major political parties from the Turkish parliament about widespread anti‐Semitic conspiracy theories regarding Dönmes (converts). The findings indicate that right‐wing political parties problematize the secret character of the Dönme commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Previous studies on the conspiracy theories about Dönmes (Nefes , , ) are in line with this version of rational choice perspective. Nefes' analyses combine values and instrumental thinking by suggesting that people and political parties logically turn ontological insecurities in Turkish politics and anti‐Semitic beliefs into conspiracy theories.…”
Section: Delineating the Political Significance Of The Conspiracy Thesupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies on the conspiracy theories about Dönmes (Nefes , , ) are in line with this version of rational choice perspective. Nefes' analyses combine values and instrumental thinking by suggesting that people and political parties logically turn ontological insecurities in Turkish politics and anti‐Semitic beliefs into conspiracy theories.…”
Section: Delineating the Political Significance Of The Conspiracy Thesupporting
confidence: 70%
“…The academic literature on the sociopolitical significance of conspiracy theories can be divided into two camps: classical‐cultural (Nefes , , , ) or symbolist‐realist (Rogin ). The classical approach delineates conspiracy theories as a political pathology and underlines how conspiracy literature leads readers to distorted, extremist views of marginal political groups (Aaronovitch ; Ben‐Itto ; Cohn ; Hofstadter ; Pipes ; Robins and Post ).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of threat were associated with greater expressions of conspiracy theories, and people proposed conspiracy theories in line with their political arguments. Nefes () uncovered similar findings in an analysis of the communication of anti‐Semitic conspiracy rhetoric in Turkey. Further, using both quantitative and qualitative content analysis, Nefes () analyzed the relationship between people’s political views and online responses to the Turkish government’s conspiracy rhetoric about the Gezi Park protests in 2013.…”
Section: Definitionsmentioning
confidence: 61%
“…Simmons and Parsons () found that elites and masses are equally likely to traffic in specific conspiracy theories, and Uscinski & Parent () found that elites and masses follow similar patterns with their conspiracy discourse. Nefes () has shown that political party members in Turkey endorse or reject conspiracy theories based upon situational and ideological factors. With this said, insiders seem to be the scapegoats of much conspiracy theorizing in Western societies, so it would seem obvious that insiders would tend to reject conspiracy thinking.…”
Section: Definitionsmentioning
confidence: 99%
“…Much of what does exist is in the political science and psychology literature. Future research within sociology might examine the perception and use of conspiracy theories by political actors (Nefes 2013), or how actors push fringe narratives into the mainstream in support of their agenda (Bail 2012). By examining how people with conspiracist beliefs reconcile them with more conventional aspects of social reality, we can gain valuable insights into the construction and maintenance of political beliefs and intersubjective reality more generally (Hoffman 2016;Garrido 2017).…”
Section: Discussionmentioning
confidence: 99%